Vibriosis in fish: a review on disease development and prevention - Ina-Salwany, MY; Al-saari, Nurhidayu; Mohamad, Aslah; Mursidi, Fathin-Amirah; Mohd-Aris, Aslizah; Amal, MNA; Kasai, Hisae; Mino, Sayaka; Sawabe, Tomoo; Zamri-Saad, Mohammad (John Wiley and Sons Inc., 2019)
Current growth in aquaculture production is parallel with the increasing number of disease outbreaks, which nega-tively affect the production, profitability, and sustainability of the global aquaculture industry. Vibriosis is among themost common diseases leading to massive mortality of cultured shrimp,fish, and shellfish in Asia. High incidence ofvibriosis can occur in hatchery and grow-out facilities, but juveniles are more susceptible to the disease. Various fac-tors, particularly the source offish, environmental factors (including water quality and farm management), and thevirulence factors ofVibrio,influence the occurrence of the disease. Affectedfish show weariness, with necrosis of skinand appendages, leading to body malformation, slow growth, internal organ liquefaction, blindness, muscle opacity,and mortality. A combination of control measures, particularly a disease-free source offish, biosecurity of the farm,improved water quality, and other preventive measures (e.g., vaccination) might be able to control the infection.Although some control measures are expensive and less practical, vaccination is effective, relatively cheap, and easilyimplemented. In this review, the latest knowledge on the pathogenesis and control of vibriosis, including vaccination,is discussed